Improving the Real-Time Concurrent Constraint Calculus with a Delay Declaration - Gerardo, M; Sarria, M (World Congress on Engineering 2012. July 4-6, 2012. London, UK, 2010)
The Real-Time Concurrent Constraint Programming Calculus (rtcc) is a model of concurrency developed to specify systems with real-time behaviour. In this paper we enhance this calculus by extending the concept of time as a discrete sequence of minimal units that we will call ticks. We also add a new construct to rtcc to be able of delaying the execution of a process for an amount of ticks. The operational semantics were adapted to support these new features. We argue that this extension makes the calculus temporally homogeneous and allows modeling real-time systems (such as an improvisation system where time is an inflexible notion) in a more precise way.